The Vulnerable Witnesses (Scotland) Act 2004 - Sharp, Laura (Lecturer in law); Ross, Margaret L. (Dundee : Dundee University Press, 2008)
This volume contains the main provisions of the Vulnerable Witnesses (Scotland) Act 2004 with a commentary informed by the authors' experience of vulnerable witnesses in practice. The Act created a new regime for civil and criminal cases so that the vulnerability of witnesses is to be considered and measures taken to support children and adults who meet the criteria of vulnerability to give evidence effectively.
Includes index.
Specialized.
Description based on print version record.
Keywords: Scotland; Examination of witnesses -- Scotland; Criminal justice, Administration of -- Scotland; Law; Laws of specific jurisdictions & specific areas of law